Utilizing Magic Finger Method in Grammar Class: Memanfaatkan Metode Jari Ajaib di Kelas Tata Bahasa - Afidah, Nurul; Ma’arif, Iin Baroroh (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of current study is improving student grammar ability by applying magic finger method. The strategy is implemented during five meetings, and in the end of meeting the grammar test is administered to get the data. After implementing the strategies in four meetings, grammar test was administered, and the result of the test was more than a half of the students can mention 16 tenses and write simple sentence both in active and passive form. Since the result of the test has met the criteria of success so that the research can be stopped in the first cycle. Another researcher can continue this study in another research design such as experimental or research development study or in another level as like on secondary level.